O TECIDO EMPRESARIAL DO TURISMO NA REGIÃO NORTE DE PORTUGAL: OS IMPACTOS DOS FUNDOS COMUNITÁRIOS EUROPEUS NO DESENVOLVIMENTO DO SETOR - Lopes, Carlos Manuel Barros (2018)
Tourism is an industry with an undeniable relevance, by the influence it exerts on the development and creation of wealth in the regions. Tourist activity generates jobs, increases income and boosts the economic growth of the receivers countries (Lim, 1997). The community structural and cohesion funds are the financial instruments of the European Union's regional policy, which aim to reduce the differences between the regions of the Member States. During the period between 2007 and 2013 the program of the National Strategic Reference Framework (NSRF) was implemented, which defines its guidelines for the national use of structural community funds and for the structuring of thematic operational program and regional. Within the framework of the NSRF, the system of incentive to innovation in the tourism sector was implemented, which aimed at the innovation of the business tissue. Given the importance of this theme, this research has as an object of study an analysis of the business tissue of the tourism sector. It aims to evaluate the economic and financial performance, the competitiveness and innovation of the entire business fabric of the tourism sector in the northern region of Portugal. A second objective is an empirical study of the impact of the incentive systems allocated in the field of NSRF to companies in the tourism sector based in the region under study. The methodology used was based on the collection of financial data relating to all active companies in the tourism sector of the northern region of Portugal, specifically 11 611 companies, during the period 2006 and 2016. The second face of the study addresses the public investment projects carried out in the tourism area in the period from 2007 to 2013 in the northern region of Portugal, comprising a total of 96 companies benefiting from the public incentive system to innovation, that integrate the thematic operational program – Competitiveness factors (COMPETE). In this sense, the study intends to assess the existence of a differential in the economic and financial analysis between the ex-ante and ex-post periods to the fund receipt. The data were collected from the Simplified Business Information (SBI), collected in the database of Iberian balance sheet analysis (SABI), a database where you can obtain official annual financial statements of Portuguese companies. From the analysis of the quantitative results we can conclude that companies generally lost competitiveness and innovation in the period under review. The results of the economic and financial indicators of the tourism sector companies based in the northern region of Portugal have decreased. With regard to the companies under study which benefited from projects approved by NSRF in the period between 2007 and 2013, we can conclude that their public investment in tourism has shown positive contributions to companies, fundamentally under the point of in view of the productivity, iv although financially it does not have any added value, these companies specifically present worse results in the financial indicators.